Semillas sometidas a radiación ionizante para la inducción de mutaciones - Correa Espinoza, Denys Katty (2021)
Mutation induction is a remarkably effective method for achieving variations within a crop type, inducing desired characteristics that cannot be found in nature or that have been lost during the evolutionary process. The purpose of this final work is to analyze the issues related to seeds undergoing treatments to induce mutations. The importance of the use of ionizing radiation in seeds has been established, as it is an issue of importance both economically and in the genetic improvement of several varieties of plants that have been used and have managed to induce all kinds of mutations, such as resistance to pests and diseases, improvement of production, flavor, colors in ornament species, better adaptation to certain environmental conditions, etc., allowing the increase in crop productivity and favoring the export and import of food. By inducing mutations with irradiation in seeds, the aim is to produce genetic changes that are beneficial for plant cultivation, Ionizing radiation is a physical agent used to treat seeds and other plant materials from crops to generate hereditary mutations; however, seed irradiation is a mechanism by which new genetic variability is generated, which can be used in genetic improvement programs, capable of creating new varieties with superior characteristics.